Comparison bending strength of simple reinforced concrete beams with bamboo reinforcement in the form of circle and square sections - Bastian Artanto Ampangallo; Dian Pranata Putra Ambali (invotek, 2021)
Steel reinforcement is well known as an important component in forming building structures. However, as the community's need for reinforcing steel is increasing, the main material for forming steel reinforcement is decreasing so that the price is getting higher. The alternative that is suggested as a substitute for tensile steel reinforcement which is economical and easy to get is bamboo. The purpose of this study was to determine the ratio of beam bending using circular and square bamboo reinforcement and to determine the bending load that can be accepted by circular and square bamboo reinforcement. In this study an experimental method was used by conducting a series of tests ranging from preserving bamboo and testing aggregates as a building block for concrete. The cross sections of bamboo reinforcement used are square and circle shapes with a diameter of 10mm with beam dimensions of 900 mm x 150 mm x 150 mm. The results showed that the flexural strength produced by steel reinforcing concrete beam was 11,36 MPa, circular cross section bamboo reinforcing beam 8,73 MPa and rectangle cross section bamboo reinforcing concrete beam of 9,04 MPa.